MEETING ROOMS NAMING IN EAST JAVA GOVERNMENTAL BUILDING: A STUDY OF ANTHROPOLOGICAL LINGUSITICS - Elvana Permataswari (Universitas Putera Batam, 2020)
Naming is a specific linguistic act, intimately linked with values, traditions, hopes, fears and events in people’s lives. Names reveal the many preferences of their owners (or givers) in terms of real life objects, actions, features and beliefs. Place names provide the most useful geographical reference system in the world. The topic of names is a multidisciplinary field that has occupied the attention of philosophers of language, anthropologists, linguists and ordinary people. In this study, I try to analyze the names of meeting rooms in the East Java Governmental Building. The reason to choose this object is because the East Java Governmental Building is the center of government/ administration in East Java. This study aims to find out the kinds of names applied in the naming of meeting rooms in the East Java Governmental Building and the presuppose reasons behind the name chosen of the East Java Governmental Building. This study is a qualitative study. Based on the classification of the data, they were classified to two groups: the names of governors in East Java and the names of the kings or military chief of great kingdoms in East Java. The meeting rooms in the governmental building of East Java are named after important people in the history of the province. To conclude, the administration named all the meeting rooms, as the most important rooms in the building to welcome guests, using the name of people who have big influence and involvement in the history of East Java so that it has roots to its history.